Provenance of the Lower Carboniferous Horton Group, Petit-de-Grat Island, Nova Scotia, as revealed by detrital zircon ages - Force, Eric R.; Barr, Sandra M. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2012)
A quartz sandstone bed in a dominantly conglomeratic section in the central part of the Lower Carboniferous Horton Group on Petit-de-Grat Island, offshore southern Cape Breton Island, Nova Scotia, contains detrital zircon grains with ages ranging from mid-Devonian to Archean. The similarity of the Devonian and Neoproterozoic age spectrum to ages of igneous units in the adjacent Avalonian Mira terrane, in particular the Coastal belt, indicates that it was the main source area. This interpretation is supported by the similarity of the Neoproterozoic and older detrital zircon age spectrum to that of the detrital zircon age spectrum in a Cambrian sandstone unit from the Mira terrane. This interpretation indicates post-depositional dextral fault motion between the Isle Madame area and the Coastal belt.